Subtidal benthic communities in Minamata Bay, Japan, approximately 30 years after mercury pollution remediation involving dredging disturbance. Issue 1 (22nd November 2021) - Yoshino, Kenji; Yamada, Katsumasa; Tanaka, Masaatsu; Tada, Yuya; Kanaya, Gen; Henmi, Yasuhisa; Yamamoto, Megumi
Abstract: Approximately 30 years after mercury pollution remediation finished in Minamata Bay, we report here the present state of the subtidal benthic communities in Minamata Bay. The benthos was sampled at stations in Minamata Bay five times between July 2018 and 2019, capturing seasonal variations. Sediment characteristics were relatively stable across seasons. Sediments contained >80% silt–clay and had total organic carbon (TOC), total nitrogen (TN), and residual total Hg content (THg) approximately 20 mg/g, 2.0 mg/g, and 2.5 mg/kg (dry‐weight basis), respectively, with a C/N ratio of ~11. THg was positively correlated with TOC, whereas TOC was negatively correlated with the C/N ratio, suggesting that TOC is a proxy for sediment microalgal matter (i.e., settling phytoplankton and/or microphytobenthos), a potential food for macrobenthos. Macrobenthos abundance was very low (approximately 100 individuals/m 2 ) and the maximum effective number of species was three in all seasons. We detected effects of THg on species richness and composition of the community, but not on total macrobenthos abundance, biomass, species diversity, or relative species abundance. The TOC gradient was significantly related to both species composition and relative abundance of the community. However, the total variation explained by both TOC and THg for community composition was low (10% at most). These results suggests that other environmental factors, such as the alteration of hydrodynamic and physicochemical regimes caused by the reclamation for pollution mitigation, may also have had a long‐lasting effect on community assembly and the present poor macrofauna levels in Minamata Bay. Abstract : The variation of benthic community structure explained by sediment characters including residual mercury was 10% at most. The effect of sediment residual mercury on the present benthic community assembly in Minamata Bay would be small.